Balys Sruoga – the first translator of Anna Akhmatova’s poetry - Ivinskaja, Aliona Sofija (Literatūra, 2019)
The article considers both the history of the creation of translations of the writer Balis Sruoga, who translated poems by Anna Akhmatova, and the translations themselves. Three verses translated by Sruoga were intended for the creative evening of the Lithuanian author in Moscow and are the first transcriptions of the Russian poet into Lithuanian. Akhmatova’s poems were part of the creative interests of the Lithuanian translator as the work of a representative of Russian modernism, not so much as a post-Symbolic plan, but rather a symbolic one. For the first time, taking into account the fact that Sruoga relied on the verbal texts of Akhmatova and their musical adaptation’s by the composer Sergei Prokofiev when translating, the analysis of the equirhythmic correspondence of the translations to the original is proposed.